Provenance and Annotation of Data and Processes 4th International Provenance and Annotation Workshop, IPAW 2012, Santa Barbara, CA, USA, June 19-21, 2012, Revised Selected Papers - Groth, Paul.; Frew, James; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the revised selected papers of the 4th International Provenance and Annotation Workshop, IPAW 2012, held in Santa Barbara, CA, USA, in June 2012. The 14 full papers, 4 demo papers and 12 poster papers presented were carefully reviewed and selected from 49 submissions. The papers are organized in topical sections on documents databases; the Web; reconstruction; science applications; and demonstrations.
Documents databases -- The Web -- Reconstruction -- Science applications -- Demonstrations.
Keywords: Computer science; Database management; Information storage and retrieval systems; Artificial intelligence; Information Systems; Computer Science; Artificial Intelligence (incl. Robotics).; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Computers and Society